2011
DOI: 10.1007/s12630-011-9649-5
|View full text |Cite
|
Sign up to set email alerts
|

An experiential teaching session on the anesthesia machine check improves resident performance

Abstract: Purpose A preoperative machine check is imperative, yet machine faults are missed despite experience. We hypothesized that a simulation training session would improve junior residents' ability to perform a machine check beyond the level of final year residents who received only didactic training. Methods In 2005, an experiential machine check training session was introduced into residency training at the postgraduate year 1 (PGY-1) level. Three weeks later, the simulation residents were asked to perform a mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Incomplete documentation about perioperative information may be taken as negligence in case there are any perioperative complications. Earlier literature reported that there were overall improvements in the filling of anaesthetic record sheets after teaching interventions 1,9,14,15 This study also supported their conclusions.…”
Section: Discussionsupporting
confidence: 87%
“…Incomplete documentation about perioperative information may be taken as negligence in case there are any perioperative complications. Earlier literature reported that there were overall improvements in the filling of anaesthetic record sheets after teaching interventions 1,9,14,15 This study also supported their conclusions.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier literatures have reported similar improved outcomes after teaching. [29,30] As spinal anesthesia technique is becoming more popular in obstetrics, anesthetists must pay attention to detail in their documentation. Although cases of litigations are rare in emerging economies including Nigeria, they may become an issue in the near future as the population becomes increasingly informed.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers can activate the classroom atmosphere and guide students to learn independently through group discussions, simulated situations, and other methods. Chiu et al [22] propose that it is easy to forget what is said from the mouths of others, but it is usually memorable and more emotional than what one has experienced. If experiential teaching wants to play a better role, it is significant to notice the fact that created situation must be consistent with the actual life and cognitive laws of students so that they can be immersed in it faster and better.…”
Section: Related Workmentioning
confidence: 99%